2012
DOI: 10.1016/j.ijgo.2011.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for failure of pelvic arterial embolization for postpartum hemorrhage

Abstract: Predictive factors significantly associated with failed pelvic arterial embolization were the presence of placenta accreta, biologic factors, and transfusional factors. Delay due to inter-hospital transfer did not affect the outcome of embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 25 publications
4
29
3
Order By: Relevance
“…Although other studies have described other potential predictors of PAE failure, including the amount of blood transfused and haemoglobin level, (18,19) these factors were not statistically significant in our study. These earlier studies were also limited by the larger number of predictive factors and the lack of multivariate analysis.…”
Section: Discussioncontrasting
confidence: 93%
“…Although other studies have described other potential predictors of PAE failure, including the amount of blood transfused and haemoglobin level, (18,19) these factors were not statistically significant in our study. These earlier studies were also limited by the larger number of predictive factors and the lack of multivariate analysis.…”
Section: Discussioncontrasting
confidence: 93%
“…Criteria of failed TAE include disseminated intravascular coagulation [18,19,75,76], major transfusion (i.e., transfusion [5 or 10 red blood cell packs), blood loss [1.5L [18,19,40], severe arterial vasoconstriction at the time of TAE [56], and invasive placenta, which has a failure rate of approximately 20 % [24,25,67]. It has been suggested that repeat TAE may be more frequently needed in women with active extravasation at initial angiography [60].…”
Section: General Results and Causes Of Failurementioning
confidence: 99%
“…This form should be used in women with retained placenta to induce thrombosis of intervillous spaces [24,66]. The use of slurry of gelatin sponge should be avoided in other situations because of reported cases of uterine necrosis with this specific material [60,67,68], although some authors have reported safe and effective TAE with slurry [65].…”
Section: Temporary and Permanent Occluding Agentsmentioning
confidence: 99%
“…(1.32), compared with 1.79 (0.9) in the unsuccessful group [38]. Although low fibrinogen is more commonly associated with specific aetiologies of bleeding, in the earlier stages of PPH from any cause it has similar predictive values.…”
mentioning
confidence: 84%